2002
DOI: 10.1002/nbm.782
|View full text |Cite
|
Sign up to set email alerts
|

The basis of anisotropic water diffusion in the nervous system – a technical review

Abstract: Anisotropic water diffusion in neural fibres such as nerve, white matter in spinal cord, or white matter in brain forms the basis for the utilization of diffusion tensor imaging (DTI) to track fibre pathways. The fact that water diffusion is sensitive to the underlying tissue microstructure provides a unique method of assessing the orientation and integrity of these neural fibres, which may be useful in assessing a number of neurological disorders. The purpose of this review is to characterize the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

75
3,409
6
36

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,112 publications
(3,604 citation statements)
references
References 129 publications
75
3,409
6
36
Order By: Relevance
“…This method is an improvement over conventional magnetic resonance imaging (MRI) in that information is provided concerning the directionality of water diffusion in brain tissue, making it a sensitive tool to detect axonal and myelin disruptions. There is also considerable evidence that less myelination results in lower diffusion fractional anisotropy (FA) (Beaulieu, 2002). We note, however, that at current levels of resolution, we cannot determine whether loss in integrity as evinced from FA measures is due to smaller diameters of axons, fewer axons, or disruptions in myelin sheaths.…”
Section: Introductionmentioning
confidence: 83%
“…This method is an improvement over conventional magnetic resonance imaging (MRI) in that information is provided concerning the directionality of water diffusion in brain tissue, making it a sensitive tool to detect axonal and myelin disruptions. There is also considerable evidence that less myelination results in lower diffusion fractional anisotropy (FA) (Beaulieu, 2002). We note, however, that at current levels of resolution, we cannot determine whether loss in integrity as evinced from FA measures is due to smaller diameters of axons, fewer axons, or disruptions in myelin sheaths.…”
Section: Introductionmentioning
confidence: 83%
“…the orientation of the local barriers created by cellular membranes, myelin sheaths, macromolecules, and so forth are directly reflected in the PDF. The shape of the PDF is also different in every position of the brain since local tissue architecture is location dependent (Beaulieu, 2002).…”
Section: Mapping the Connectome With Mrimentioning
confidence: 99%
“…In order to better utilize this promising technology, it is important to understand the basis of the anisotropy contrast in DTI and the limitations imposed by using a macroscopic technique to visualize microscopic restrictions. These basics are briefly reviewed, while a more comprehensive overview is presented by Beaulieu et al 43 Recent technologies that have been demonstrated to allow the visualization of three-dimensional (3D) fiber tracts are reviewed and discussed with respect to their potential and limitations regarding the determination of propagation, termination, branching and editing of tracts. Limitations and several techniques that may minimize them are described.…”
Section: Introductionmentioning
confidence: 99%